Risk of recurrence after a first unprovoked seizure in children - Catarina Maia; Ana Raquel Moreira; Tânia Lopes; Cecília Martins
Abstract Objectives: This study aimed to evaluate the first episode of unprovoked epileptic seizure in children and assess recurrence risk factors. Methods: This was a retrospective observational study, based on the analysis of medical records of patients admitted between 2003 and 2014, with first epileptic seizure, at the pediatric service of a secondary hospital. The data were analyzed using the SPSS 20.0 program. Results: Of the 103 patients, 52.4% were boys. The median age at the first seizure was 59 (1-211) months. About 93% of children were submitted to an electroencephalogram at the first episode and 47% underwent neuroimaging assessment. Treatment with an antiepileptic drug was started in 46% of patients. The recurrence rate was 38% and of these, 80% had the second seizure within six months after the first event. Of the assessed risk factors, there was a statistically significant association between seizure during sleep and recurrence (p = 0.004), and between remote symptomatic etiology seizure and occurrence of new seizure (p = 0.02). The presence of electroencephalogram abnormalities was also associated with the occurrence of new seizures (p = 0.021). No association was found between age, duration of the seizure, and family history of epilepsy with increased risk of recurrence. Conclusions: Most children with a first unprovoked epileptic seizure had no recurrences. The risk of recurrence was higher in patients with seizure occurring during sleep or remote symptomatic ones and those with abnormal electroencephalogram results.